An integrated breast cancer risk assessment and management model based on fuzzy cognitive maps. Issue 3 (March 2015) - Subramanian, Jayashree; Karmegam, Akila; Papageorgiou, Elpiniki; Papandrianos, Nikolaos; Vasukie, A.
Graphical abstract